IS ISLAMIC BANKING PERFORMANCE IN MALAYSIA TRULY BETTER THAN INDONESIA? - Naja, Abdul Hakam; Indiastuti, Rina; Masyita, Dian; Cupian, Cupian (Journal of Islamic Monetary Economics and Finance, 2023)
This article analyzes the performance of Islamic banking in Malaysia and Indonesia using a comprehensive evaluation framework. Malaysia is known for its leading role in Islamic finance, while Indonesia has faced criticism for slower growth. The study argues that assessing Islamic banking performance solely based on financial metrics is insufficient and proposes a broader framework based on the Maqasid Shariah (objectives of Islamic law) for a more objective standard. Using data from 2010 to 2019, the study constructs a Maqasid Shariah Index of Islamic Bank (MSI-iB) and adopts a T-test as well as a panel data model to evaluate their performance. The index includes five sub-indices representing different aspects of the Maqasid Shariah framework. Results show varied scores among Islamic banks in both countries with no statistical difference between the two countries, but with Indonesia leading in religiosity and intellectuality dimensions and Malaysia leading in the posterity dimension. These results challenge the perception that Malaysia's Islamic banking performance is inherently superior to Indonesia's based solely on financial metrics. Considering the Maqasid Shariah framework is crucial to evaluating Islamic banking performance, highlighting the significance of non-financial indicators. The study concludes that a comprehensive perspective is necessary, incorporating both financial and non-financial factors, to assess overall performance.